Students’ Creative Thinking Skills on Heat Phenomena Using POGIL Learning Model - Pratiwi, Rinta Dian; Ashadi, Ashadi; Sukarmin, Sukarmin; Harjunowibowo, Dewanto (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
This research aimed to analyze the improvement of students' creative thinking skills on the topic of heat and its transfer using the POGIL model. The matter concerning heat and its transfer has some characteristics that enable students to carry out practicum and trigger them to develop their higher-order thinking skills. The method used in this research was pre-experimental with one group pretest-posttest design. A total of 32 seventh grade students at SMPN 1 Jaten Karang Anyar, Central Java, were randomly selected as the participants in this research. To measure the increase in students' creative thinking skills, a multiple-choice test had been developed based on the indicators of creative thinking skills. Based on the results of data analysis, the values of N-gain on the indicators consisting of fluency, flexibility, originality, and elaboration were 0.56, 0.60, 0.46, and 0.53, respectively. Those numbers meant that creative thinking was in the medium category. Further analysis shows that, by using the POGIL model on the topic of heat and its transfer learning, students’ creative thinking skills can be increased, especially on the indicators of fluency and flexibility.